Efektivitas Dan Adaptasi Tumbuhan Eceng Gondok Dalam Menurunkan Kadar BOD Dan COD Dalam Limbah Cair Pabrik Kelapa Sawit - Mutmainah Mutmainah; Zainudin Basri; Syamsuddin Laude (Mitra Sains, 2019)
This research was conducted to determine the effectivity of water hyacinth (Eichhornia crassipes (Mart.) Solms,) on reducing Biohemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) content in Palm Oil Mill Effluent (POME) and find out water hyacinth’s adaptation after contact to POME for 21 days. This research was conducted in September to November 2017 at PT. Manakarra Unggul Lestari, Mamuju, West Sulawesi. This research was arranged on Block Randomized Design, consist of four treatments: P0=0 clumps of water hyacinth, P1=5 clumps of water hyacinth, P2=10 clumps of water hyacinth and P3=15 clumps water hyacinth in strerofoam box contains 105,000 cm3 POME/box treatment and repeated 3 times, resulting 12 experimental units. Wet weight, dry weight, root volume, stomata index and chlorophyll content of water hyacinth were measured to determine the adaptation of water hyacinth after contact with liquid waste. The research results showed that water hyacinth is effective on reducing BOD and COD content in POME. P3 was the largest BOD and COD decrease level, BOD was decreases to 97.36% and COD decreases to 97.50%. From the research can be concluded that water hyacinth plants were able to adapt when placed in the POME and did not show significant signs of stress